Effects of Dietary Inclusion of Ginger (Zingiber Officinale) and Garlic (Allium Sativum) Oil (GGO) Mixtures on Carcass Characteristics and Sensory Evalaution of Broiler Chickens - R. A Oluwafemi; Aisha Omolade Lawal; Adelowo Samad Adetope; J. O Alagbe (Newinera Publisher, 2021)
An experiment was conducted to assess the influence of GGO on carcass features and sensory assessment of broiler chickens. 120 1-day-old (Arbo acre) birds were separated into five treatments, each with three replicates of 8 birds. Throughout the 8-week trial, clean feed and water were available at all times. NRC's basal diet was designed to suit avian nutritional needs (1994). A 0% GGO meal was given to the birds in treatment 1, whereas GGO levels of 0.1, 0.2, 0.3 and 0.4 percent were given to the birds in treatments 2, 3, 4, and 5. As well as studying the phytochemical content of (Zingiber officinale) and garlic (Allium sativum) oil, carcass and organ features of birds were also studied. Zingiber officinale contains phenols (8.21%), alkaloids (5.12%), flavonoids (7.49%), tannins (6.52%), saponins (3.18%), streiods (2.38%), glycosides (0.18%), oxalates (0.07%), and phytate (0.07%). (0.02 %). Sativum contains flavonoids (10.67%) alkaloids (7.02%) tannins (4.72%) steroids (3.65%) saponin (2) glycoside (0.33%) oxalates (0.26%) and phytate (0.26%). (0.05 %). Dressing %, carcass and relative organ weights differed across treatments (P0.05). The liver, kidney, spleen, and other internal organs showed no signs of inflammation. GGO altered meat sensory assessment (tenderness, juiciness, taste, and fragrance) except meat color which was not significantly (P0.05) different across treatments. GGO may be fed to broilers up to 0.4 percent without affecting their health or performance.